Colloidal co‐assembly of dual‐phased ceramic/metal particles toward lightweight, hierarchically structured, and mechanically robust alumina foam. Issue 10 (5th June 2022) - Ren, Bo; Liu, Jingjing; Li, Bin; Liu, Chuanbao; Chen, Haiyang; Liu, Jie; Li, Guangqi; Chen, Junhong
Abstract: Ceramic foams constructed by aqueous‐based foam templating have demonstrated great potential in industrial and research applications. However, a multiple‐phased suspension with inherently improved complexity inevitably leads to a severe deterioration of foam stability. Herein, we proposed a colloidal co‐assembly strategy that introduces Al–Al2 O3 dual‐phased particles for constructing ultralight yet mechanically robust cellular ceramics. Owing to the Al2 O3 oxidation layer on Al particles, both of Al and Al2 O3 suspensions demonstrated similar zeta potential and rheological properties, enabling a stable foam structure after colloidal co‐assembly. High‐temperature oxidation of Al particles contributed to the reinforcement of cell wall and formation of Al2 O3 whiskers. The calcined products demonstrated a lightweight structure (0.31 g cm −3 ), a robust compressive strength (3.64 MPa) at a porosity level of 88.5%, and a relatively high specific surface area (14.7 m 2  g −1 ). The current strategy paves the way for the construction of high‐performance ceramic foams for a broad range of applications.